2022
DOI: 10.37268/mjphm/vol.22/no.1/art.1519
|View full text |Cite
|
Sign up to set email alerts
|

Photovoice Method Trends, Status and Potential for Future Participatory Research Approach

Abstract: In the last decade, researchers from around the world have shown deep interest in using photovoice as a method of analysis in scientific research. This might be due to the participatory strength of the method that acts as a bridge to connect researcher and community by balancing scientific research and mitigating action. The purpose of this research is to synthesize the available research on the photovoice method using the Scientometric method. This article explores the research landscape,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…inside the network. A network is a string of nodes (a document, author, affiliation and country of published article) that are intercorrelated with one another via ties (lines that link two or more nodes with each other, where the link represents the citation that an article gives or obtains from other articles) [17][18][19]. Chen, a researcher at the College of Computing and Informatics, Drexel University, USA, and was freely available from the CiteSpace website (https://citespace.podia.com/download) (accessed on 3 October 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…inside the network. A network is a string of nodes (a document, author, affiliation and country of published article) that are intercorrelated with one another via ties (lines that link two or more nodes with each other, where the link represents the citation that an article gives or obtains from other articles) [17][18][19]. Chen, a researcher at the College of Computing and Informatics, Drexel University, USA, and was freely available from the CiteSpace website (https://citespace.podia.com/download) (accessed on 3 October 2022).…”
Section: Methodsmentioning
confidence: 99%
“…inside the network. A network is a string of nodes (a document, author, affiliation and country of published article) that are intercorrelated with one another via ties (lines that link two or more nodes with each other, where the link represents the citation that an article gives or obtains from other articles) [17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…This photographic technique was developed to give voice (Wang & Burris, 1997) to politically and socially marginalized populations through photographs they take of their everyday lives and experiences, discussing the meanings behind those images and articulating that they can disseminate their findings directly with stakeholders, supporting local action (Hess et al., 2020; Musoke et al., 2015; Watchman et al., 2020). The method is gaining popularity in the health science (Lindhout et al., 2021; Noor et al., 2022) especially in the field of public health (Budig et al., 2018; Chavez‐Baray et al., 2022), as a tool to claim the iii) principle of reaching out to policy makers or influencing policy change.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies can help to know the current status of research through citation analysis, covering correlation between journals and literature, as well as important keywords and cluster analysis, and can ultimately help researchers grasp a global perspective and reveal research hotspot and knowledge gaps in certain research areas (Zhang, Zou, 2022). Any research gaps and/or potential future studies can be identified through indepth bibliometric analysis such as document burstness, co-citation comparison, dual map overlay, keywords' distribution, and contributors' analysis (Aryadoust et al, 2019;Azra et al, 2022;Chen, 2017;Chen, Song, 2019;Noor et al, 2022). Scientometric reviews of literature have been conducted on themes ranging from specific issues, for example, carbon emissions (see Udara Willhelm Abeydeera et al 2019), to researchers, for example, Professor Wolfgang Glanzel (Gholampour, Noruzi, 2021), taxa, for example, zebrafish (see Kinth et al 2013), or organizations, for example, Iranian Orthopedics Academic Departments (see Ebrahimpour et al 2021).…”
Section: Introductionmentioning
confidence: 99%